2011
DOI: 10.5402/2011/892971
|View full text |Cite
|
Sign up to set email alerts
|

Importance of IL-10 Modulation by Probiotic Microorganisms in Gastrointestinal Inflammatory Diseases

Abstract: Lactic acid bacteria (LAB) represent a heterogeneous group of microorganisms that are naturally present in many foods and possess a wide range of therapeutic properties. The aim of this paper is to present an overview of the current expanding knowledge of one of the mechanisms by which LAB and other probiotic microorganisms participate in the prevention and treatment of gastrointestinal inflammatory disease through their immune-modulating properties. A special emphasis will be placed on the critical role of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(75 citation statements)
references
References 93 publications
0
73
0
2
Order By: Relevance
“…these patients [37]. IL-10 is an anti-inflammatory cytokine that is involved in the suppression of the release of proinflammatory cytokines such as TNF-, interferon-(IFN-) and IL-1 [38]. Recently, the first pediatric, randomized, placebo-controlled trial using this probiotic mixture in patients with ulcerative colitis was published.…”
Section: Rhamnosus Gg L Rhamnosusmentioning
confidence: 99%
“…these patients [37]. IL-10 is an anti-inflammatory cytokine that is involved in the suppression of the release of proinflammatory cytokines such as TNF-, interferon-(IFN-) and IL-1 [38]. Recently, the first pediatric, randomized, placebo-controlled trial using this probiotic mixture in patients with ulcerative colitis was published.…”
Section: Rhamnosus Gg L Rhamnosusmentioning
confidence: 99%
“…It is well known that IL-10 down-regulates inflammatory cascades through the suppression of pro-inflammatory cytokines. However, oral treatment with IL-10 is difficult because of its low half-life in the gastrointestinal tract (GIT), and systemic treatments have not been proven effective in inducing clinical remission and have been associated with undesirable side effects [de Moreno de LeBlanc et al, 2011]. For these reasons, some groups have proposed the use of IL-10-producing LAB for the local delivery of this cytokine in the GIT and to prevent the risks associated to systemic administration [Li and He, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…These advances have led to the creation of interesting strains, some of which have recently been tested using different inflammation animal models confirming their potential for the prevention and treatment of IBD [Carroll et al, 2007;Han et al, 2006;LeBlanc et al, 2011;Rochat et al, 2007;Watterlot et al, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…In vivo study using dextran sulfate sodium-induced colitis mice model revealed that L. lactis strain prevented the colitis, and proved that L. lactis is safe for human. [24,25] Some of the studies suggested that administration of LAB or IL-10 producing LAB mediated fermented food nullify the consequences of colitis in mice. [26,27] The oral supplementation of Lactobacillus HY7801 introverted the colon shortening and myeloperoxidase activity in 2, 4, 6-trinitrobenzenesulfonic acid-induced colitic mice, and decreased the expression of IL-1β, IL-6, and tumor necrosis factor-alpha, [28] which indicated that LAB could suppress the initiation or development of colitis.…”
Section: Discussionmentioning
confidence: 99%